SCIENTIFIC AND PRACTICAL ASPECTS OF ORGANIZING CATERING SERVICES WITH CONSIDERATION OF FOOD SAFETY AND INTERNATIONAL STANDARDS - Овсянніков, Ю. (SWorldJournal, 2025)
The paper examines the organizational and technological components of the implementation of catering services in the context of compliance with international food safety standards, in particular HACCP, ISO 22000 and GMP. The purpose of the study is to stu